(untitled) (Revista Direito em Debate, 2022)
Water management and governance has been one of the most serious problems to be faced in this millennium. In this wake, water transposition has been presented to solve a scarcity scenario. However, it is necessary to take into account the problems that still exist in water management and governance, such as fragile decentralization, the absence of solid planning, trained people and participation. Therefore, the research question that arises is to what extent has the management and governance of the east axis of the transposition been carried out within minimum compliance parameters? It is intended to characterize the application of the term management and governance in the case of the transposition of the São Francisco River, analyzing the performance of the actors involved in this dynamic in the context of rules to be followed, verifying the extent to which compliance indicates the failures of this complex process water transfer in the case of the east axis. This is done through a bibliographic survey and document analysis. There is a lack of a management and governance structure that can predict risks and effectively solve problems that occur in works of this magnitude. It is necessary to implement a compliance system in the management and governance of the east axis of the transposition.